The Effect of Intellectual Capital on Business Performance in Micro-, Small-, and Medium Enterprise (MSME) in Medan City - Absah, Y; Chairunisa Muchtar, Y; Qamariah, I (KnE Social Sciences, 2018)
The Ministry of Cooperative and SME discloses currently the number of SME is 56.5 million units and 98.9% is micro, one of which is fashion business that is needed by the people (HTTPS://www.antaranews.com). The phenomenon of people’s demand for clothing has become an opportunity for the creative industry community to develop a business in the fashion industry by presenting the fulfillment ground for clothing shopping. The objectives of this research are to analyze the influence of Intellectual Capital on Business Performance and to analyze the influence of Human Capital, Technological Capital, Customer Capital, and Social Capital partially on Business Performance. The sample of this study is 76 MSME in fashion industry that have operated for more than two years and specifically along Universitas Sumatera Utara. Result shows that intellectual capital has a positive and significant effect on business performance. Human capital, technological capital, and social capital partially have positive and significant effect on business performance. While customer capital has insignificant effect on business performance. In general, MSMEs owner and manager should focus in improving intellectual capital strategy in order to improve the business performance. Keywords: intellectual capital, business performance, human capital, technological capital, customer capital, and social capital